Prolonged interval between parturition of normal live pups in a bitch - Romagnoli, S.; Souza, Fabiana Ferreira de [UNESP]; Rota, A.; Vannozzi, I (British Veterinary Assoc, 2004)
On day 64 after artificial insemination, a six-year-old primiparous briard bitch whelped three live pups between 05.00 and 08.00. It was presented at 11.00 on the same day with failure to complete parturition. on ultrasound examination, a normal live fetus was observed and the bitch was treated with oxytocin three times during the day (1(.)0, 2(.)0 and 2(.)0 iu intramuscularly), with no effect. The following day, a higher dose of oxytocin (5(.)0 iu) was administered intramuscularly at 11.00, after a uterine ultrasound examination confirmed viability of the fetus. At 18.00 of the same day, the bitch whelped the fourth normal live pup, 37 hours after initiation of parturition and 34 hours after expulsion of the last fetus. Effectiveness of oxytocin and normal versus prolonged parturition due to uterine inertia are discussed.